Laparoscopic Decortication of Hilar Renal Cysts Using LigaSure - AKÇAY, MUZAFFER; Erdem, Mehmet Remzi; Tepeler, Abdulkadir; Gunes, Mustafa; Silay, Mesrur Selcuk; Akman, Tolga; AKÇAY, MUZAFFER; Armagan, Abdullah; Onol, Sinasi Yavuz (My University, 2014)
Background and Objectives: In this study, we evaluated the safety and efficacy of using the LigaSure sealing system (Valleylab, Boulder, Colorado) for laparoscopic decortication of symptomatic hilar renal cysts.